5(x+8)=-7+8(x-1)

Simple and best practice solution for 5(x+8)=-7+8(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+8)=-7+8(x-1) equation:



5(x+8)=-7+8(x-1)
We move all terms to the left:
5(x+8)-(-7+8(x-1))=0
We multiply parentheses
5x-(-7+8(x-1))+40=0
We calculate terms in parentheses: -(-7+8(x-1)), so:
-7+8(x-1)
determiningTheFunctionDomain 8(x-1)-7
We multiply parentheses
8x-8-7
We add all the numbers together, and all the variables
8x-15
Back to the equation:
-(8x-15)
We get rid of parentheses
5x-8x+15+40=0
We add all the numbers together, and all the variables
-3x+55=0
We move all terms containing x to the left, all other terms to the right
-3x=-55
x=-55/-3
x=18+1/3

See similar equations:

| 2.5x+10=0.5 | | 13+20-9x-2=30 | | 7.8+x=19.2 | | 2/7=x/2 | | y2-11y+30=0 | | A=3.14x1 | | 11x+15x-8+1=-8x+1-8 | | 6w+56=13w | | 9-6z=-8-6z | | 3x-24=6x+48 | | 19h=6h−13 | | 2/9x=27 | | 6.5a=32. | | x.6-4=12 | | 2(g+1)=7 | | 7=35t−27=35t-2 | | 3x+12+3=6 | | 540=-70*3+x | | 5y=48+ | | 8=5n-2+2+ | | 3x+4+5x-x+7=88 | | 14x=15x-9+16 | | g^2+3g-180=0 | | -8x-2*5=70 | | 3n(2+n)=6 | | -5s/2+100=0 | | 15x^2-1x-6=0 | | 0.10v=5 | | -5s/2+100=95 | | 15x^2-1-6=0 | | -11x-44=25 | | −1-2c=4 |

Equations solver categories